PS6:116 Diet habits in patients with systemic lupus erythematosus. (21st March 2018) - Petric, M; Radic, M; Perkovic, D; Bozic, J; Petric, M; Marasovic Krstulovic, D; Boric, K; Bozic, I; Erceg, I; Martinovic Kaliterna, D
Abstract : Objective: Many patients with systemic lupus erythematosus (SLE) are interested in diet advices. We wanted to investigate which diet habits are most common in our patients, and which of them are in correlation with laboratory parameters that are related to disease remission, such as normal values of serum complement and 24 hour proteinuria. Methods: We included 76 patient with SLE in remission, in age between 21 and 75. They fulfilled 23-item questionnaire about weekly diet habits. Basic anthropometric data, disease duration, levels of C3 and C4 complement components and 24 hour proteinuria were recorded and analysed in correlation with diet habits. Results: Majority of our patients had normal BMI (between 18.5 and 25 kg/m2), prefered to eat healthy food and did regular weekly workout. Milk, meat, fruits, vegetables, pasta, rice and bread were the most abundant food. Lower serum values of C3 were found in 34 (44.7%) cases, and lower values of C4 were found in 28 (36.8%) cases. Only 5 (6.6%) patients had significant 24 hour proteinuria higher than 3.5 g and another 7 (9.2%) had proteinuria higher than 1 g. Lower values of C3 were found in patients who often consumed meat (p=0.015) and fast food (p=0.060), and those patients who more often consumed fast food or fried food had lower levels of C4 (p=0.043 and p=0.051). Conclusions: There is an evidence that food rich in proteins and calories can lower serum complement levels. As clinicians, we should always advice our SLE patients to eat a lot of fish, fruits and fresh vegetables, although there is no strong support for that. More studies with dietary interventions have to be done before final recommendations can be made.